Measurement of Patellar Proximodistal Positioning with Limited Joint-Angle Sensitivity - Allberg, Clara M.; Miles, James (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective Patellar luxation can be associated with abnormal proximodistal positioning of the patella. The current gold standard index (Insall–Salvati) for referencing this position is poorly suited to postoperative use, if the tibial tuberosity is moved surgically, but has the advantage of changing minimally with altered joint angles. The aim of this study was to identify an alternative index, which was simple to use, joint-angle insensitive and suitable for postoperative use.Study Design Candidate indices based on the angle between stifle joint landmarks were screened across a wide range of joint angles for insensitivity to joint angle changes using vulpine and canine stifle radiographs. Intraobserver and interobserver agreements were assessed for a single candidate index using canine radiographs.Results An angular index based on the caudal aspect of the femoral and tibial condyles and the apex of the patella was largely insensitive to joint angle variation. Intra- and interobserver agreements appeared suitable for clinical use, with low within-subject standard deviations (<1.3°) and coefficients of variations (<2.2%), and high intraclass correlation coefficients (>0.89).Conclusion Patellar proximodistal position can be acceptably assessed at a variety of caudal joint angles using the described angular index. Further work is required to define reference intervals across a range of canine breeds.
Keywords: patella luxation; radiographs; dogs